Bio-Derived Carbon with Tailored Hierarchical Pore Structures and Ultra-High Specific Surface Area for Superior and Advanced Supercapacitors - Fuming Zhang; Xiangshang Xiao; Dayakar Gandla; Zhaoxi Liu; Daniel Q. Tan; Yair Ein-Eli (Nanomaterials, 2021)
We report here on a hollow-fiber hierarchical porous carbon exhibiting an ultra-high specific surface area, synthesized by a facile method of carbonization and activation, using the Metaplexis Japonica (MJ) shell. The Metaplexis Japonica-based activated carbon demonstrated a very high specific surface area of 3635 m2 g−1. Correspondingly, the derived carbonaceous material delivers an ultra-high capacitance and superb cycle life in an alkaline electrolyte. The pore-ion size compatibility is optimized using tailored hierarchical porous carbon and different ion sized organic electrolytes. In ionic liquids nonaqueous based electrolytes we tailored the MJ carbon pore structure to the electrolyte ion size. The corresponding supercapacitor shows a superior rate performance and low impedance, and the device records specific energy and specific power densities as high as 76 Wh kg−1 and 6521 W kg−1, as well as a pronounced cycling durability in the ionic liquid electrolytes. Overall, we suggest a protocol for promising carbonaceous electrode materials enabling superior supercapacitors performance.